Állami növénynemesítés és kultúrnövényeink biodiverzitása - Matuz, János (Jelenkori Társadalmi és Gazdasági Folyamatok, 2011)
Crop production (including that of field crops, vegetables, fruits, grapes, medicinal plants and herbs) constitutes the basis of food supply and food industry and its economic interest is to main tain and expand the biodiversity of cultivated plants to meet the dem and of the market and production technology. The globalization, the EU-membership, the immigration and the tourism trigger the incessant broadening of the assortment of cultivated plant species and varieties. The most reliable and efficienttool to maintain and develop the biological base of our cultivated plants is to sustain and enhance the domestic plant breeding. It is the domestic plant breeding through which plant varieties best adapted to the domestic land and climate and the demand of growers, users and consumers can be created. Based on the National List of Varieties 2010, the study reviews the breeding results of the cultivated plants at the state-owned research institutes. It delineates the major problems of the breeding institutes and outlines the potential solutions of these problems as well.